1969
DOI: 10.1038/sc.1969.31
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the cervical spine following the conservative treatment of fractures and fracture-dislocations

Abstract: There are many classifications of injuries of the cervical spine. This is not the place to debate their merits and demerits. Suffice it to say that in this paper the classification used is broadly based on that proposed by Holdsworth (1963), and also relates to the work of Roaf (1960) and Beatson (1963), whose important experimental work increased the general understanding of the mechanisms involved. However, and this point must remain to be argued later, it is felt that these authors oversimplify flexion-rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

1971
1971
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 7 publications
2
20
0
2
Order By: Relevance
“…Of the six cases with congenital fusion, three injuries were caused by Many authors have reported the phenomenon of rapid bony consolidation of injuries to the ankylosed cervical spine. They include Ackerman (1972), Bergmann (1949), Cheshire (1969), Good (1967), Grisolia et al (1967) and Rand and Stern (1961). Our experience (Table IV) substantiates their observations.…”
Section: Mechanism Of Injurysupporting
confidence: 86%
See 2 more Smart Citations
“…Of the six cases with congenital fusion, three injuries were caused by Many authors have reported the phenomenon of rapid bony consolidation of injuries to the ankylosed cervical spine. They include Ackerman (1972), Bergmann (1949), Cheshire (1969), Good (1967), Grisolia et al (1967) and Rand and Stern (1961). Our experience (Table IV) substantiates their observations.…”
Section: Mechanism Of Injurysupporting
confidence: 86%
“…Our experience is consistent with the observation of authors who have previously stressed this important clinical point. They include Guttmann (1966), Burke (1971), Cheshire (1969), Taylor (1953), Brain andWilkinson (1967), Symonds (1953), Osgood et al (1973, 1975, Rand andStern (1961), Schneider et al (1954), and Woodruff and Dewing (1963). All eight of our cases of ankylosing spondylitis had historical or radiographic evidence of an extension mechanism.…”
Section: Mechanism Of Injurymentioning
confidence: 70%
See 1 more Smart Citation
“…They are characterised by descriptions based on X-rays or classifications according to the assumed genesis (Cheshire, 1969;Holdsworth, 1970) and do not have as bad a reputation as injuries in the upper cervical region, but they may be as sociated with tetra-or paraparesis. In the present study injuries to the C5 level showed the most frequent association with tetraparesis.…”
Section: % (Amyes and Anderssonmentioning
confidence: 99%
“…However, studies comparing this technique with posterior procedures show that anterior decompression and fusion has a higher incidence of complications (Bedbrook, 1966;Cheshire, 1969;Meyers, 1967;Stauffer, 1977;Van Peteghem 1979). Two prior studies have documented a low incidence of graft displacement or late kyphosis, but they included only a limited number of patients with unstable injuries (Cloward, 1969;Meyers, 1967).…”
mentioning
confidence: 99%